Content Marketing Analysis of Bank Syariah Indonesia : A Literature Study on Successful and Effective Content Marketing Strategies - Nursamawi Nursamawi; Hartanti Nugrahaningsih (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study aims to analyze the implementation of content marketing strategies in the Islamic banking industry in Indonesia, with a focus on the effectiveness of content in enhancing audience engagement and building the image of Islamic brands. The research was conducted through a literature review of various academic sources and previous studies, as well as an analysis of the content marketing of Bank Syariah Indonesia (BSI) on its YouTube channel as the main object. In the digital context, the types of content used include educational videos, marketing videos, and collaborations with influencers. The findings indicate that visual, educational, interactive, and authentic content has a significant impact on driving digital engagement and increasing brand awareness. Meanwhile, promotional content delivered through influencers tends to be more effective when preceded by strong brand image reinforcement, enabling consumers to develop a more positive perception of the institution. Further analysis reveals that BSI’s YouTube channel has demonstrated consistency in branding, Islamic positioning, and delivering educational messages. However, audience interaction remains limited, as reflected in the minimal responses to comments, underutilization of community features, and subscriber growth lagging behind major banks such as BCA. This situation highlights the need to optimize strategies through strengthening two-way communication, delivering serial educational content, employing more strategic calls-to-action (CTA), and integrating with the official website and other digital platforms.The study concludes that the success of content marketing in Islamic banking heavily depends on value relevance, publication consistency, and the ability to build sustainable interaction with audiences, thereby supporting increased loyalty and customer acquisition. These findings provide important contributions to designing effective and sustainable digital communication strategies that align with ethical principles and Islamic values.